CRITICAL DISCOURSE ANALYSIS OF ONLINE MEDIA NEWS: MINISTRY OF RELIGIOUS AFFAIRS BANNING ARABIC LANGUGE - Laila Nabilal Huda (Leksema: Jurnal Bahasa dan Sastra, 2022)
The purpose of this research was to describe the micro, mezzo, and macro linguistic aspects of the news discourse ‘Ministry of Religious Affairs banning Arabic language’ on Tempo.co and Republika online media. The news topic has emerged a polemic among the madrasas or Islamic school environments. It is because there are a lot of Indonesian muslim children study at the schools. This research applied descriptive-qualitative method with critical discourse analysis (CDA) approach. The analysis was divided into three dimensions, namely the micro, mezzo, and macro. From the microdimension, in Tempo news, there were found four data of modalities and each two for positive evaluation sentences and assertive verbs. Meanwhile, in Republika, there are two data of modalities and only one from each metaphor and negative evaluation sentence. In the mezzodimension, the scope of Tempo's discourse is not only restricted to the issue on the prohibition of using Arabic language but also of using hijabs or veils. On the other hand, the news of Republika focuses on the banning of Arabic language without associating it to another case. In the macrodimension, both news texts show an alignment to the government, particularly Ministry of Religious Affairs.